MANAJEMEN TEMPAT TUMBUH PADA TANAMAN Eucalyptus pellita DI PT. PERAWANG SUKSES PERKASA INDUSTRI, DISTRIK LIPAT KAIN, RIAU Site Management Eucalyptus pellita at PT. Perawang Sukses Perkasa Industri, Riau - Prijanto Pamoengkas; Puspita Laksmi Maharani (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2018)
Eucalyptus sp. is species which the developed in forest plantation of Indonesia as wood fiber plantation. Wood fiber for pulp and paper is important, so we need to know management of site to obtain the optimal growth of Eucalyptus pellita at PT. Perawang Sukses Perkasa Industri (PSPI). The aim of the research was to observe fertilization management and maintenance management at PT. PSPI. This research used Forest Health Monitoring (FHM) method to take data of plant growth. The cluster had 4 plot. The sample was E. pellita 1-4 years. Fertilization management at PT PSPI were basic fertilizer (CIRP/Cristmast Island Rock Phosphate and NPK) and supplementary fertilizer (NPK-1, NPK2, NPK-3). Maintenance Management at PT. PSPI were ring weeding, sport spray of herbicide and slash. Maintenancing and fertilizing were given to the plot according to the environmental conditions and the age factor. The best growth increment was in plot P2. P2 had 4.14 diameter increment and 5.72 height increment.Keywords: Eucalyptus pellita, Forest Health Monitoring, Industrial forest, site management, maintenance management, fertilization management